Pyrolysis 2017
DOI: 10.5772/67865
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Pyrolysis in a Stage Scheme of Low‐Grade Solid Fuel Gasification

Abstract: This paper is concerned with the development of a model of wood pyrolysis in a screw reactor as the first stage of the multistage gasification process. In terms of design, the pilot pyrolyzer represents a recuperative heat exchanger where the heat carrier is represented by a mixture of exhaust and recirculation gases. To prevent clinkering of particles and thermal inhomogeneities, screw-type transportation is used to transport fuel. In order to describe kinetics of pyrolysis and transport of volatiles within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A Kronwerk LK 1500 gasoline generator modified for operation on generator gas is used as an electric generator. Experiments have shown that the power obtained with the use of generator gas in the stationary mode is 60-80 % of the nominal, at a voltage of 220±20 V, and the efficiency(e) is 22 % [5,6].…”
Section: Gas-fired Power Plantmentioning
confidence: 99%
“…A Kronwerk LK 1500 gasoline generator modified for operation on generator gas is used as an electric generator. Experiments have shown that the power obtained with the use of generator gas in the stationary mode is 60-80 % of the nominal, at a voltage of 220±20 V, and the efficiency(e) is 22 % [5,6].…”
Section: Gas-fired Power Plantmentioning
confidence: 99%